Evaluation of treatment methods for eradication of plant pathogens from carrot seed - Cheah, L-H.; Olsson, S. (New Zealand Plant Protection, 2008)
Importation of seed is a risk pathway for the introduction of unwanted organisms to New Zealand including pathogens insects and weeds These risks are managed by MAF BNZ through implementation of Import Health Standards but information about the efficacy of some seed treatments is lacking Alternaria leaf blight and Fusarium root rot of carrot (caused by Alternaria and Fusarium spp respectively) are seedborne diseases and can cause seed losses of up to 50 Treatment methods tested for control of these diseases included ozone (in gas or in water) at 10 ppm for 10 30 and 60 min for each treatment; ionised copper water at 5 ppm for 2 4 and 8 h; and hot water drench at 50 525 and 55C for 15 and 30 min at each temperature Treated seeds were plated on PDA with antibiotics and fungi growth assessed 5 days after incubation at 22C None of the ozone and ionised copper water treatments reduced frequency of isolation of Alternaria and Fusarium spp All hot water drench treatments (except 50C for 15 min) completely killed the fungi These results indicate that hot water treatment is effective for control of Alternaria and Fusarium spp on carrot seeds The effect of hot water treatments on seed germination is being investigated